If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46.11 = 6s + 4.89 Reorder the terms: 46.11 = 4.89 + 6s Solving 46.11 = 4.89 + 6s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6s' to each side of the equation. 46.11 + -6s = 4.89 + 6s + -6s Combine like terms: 6s + -6s = 0 46.11 + -6s = 4.89 + 0 46.11 + -6s = 4.89 Add '-46.11' to each side of the equation. 46.11 + -46.11 + -6s = 4.89 + -46.11 Combine like terms: 46.11 + -46.11 = 0.00 0.00 + -6s = 4.89 + -46.11 -6s = 4.89 + -46.11 Combine like terms: 4.89 + -46.11 = -41.22 -6s = -41.22 Divide each side by '-6'. s = 6.87 Simplifying s = 6.87
| -3-5n+4n-2= | | x-9=41 | | 414.30=240+0.83x | | 17u-19u+16u=14 | | 3x+5+6x=4x-15 | | 1n+1.50=0.50+4.50 | | 8n+2=11n-16 | | 2c-4=16 | | 2w-10w=8 | | 5n-6n-7+4= | | -2(3x-4)+(4x)=18 | | 56a+8b=40 | | (3x-2)(12x+7)=0 | | 2.02b+4.30=2.00+6.30 | | 10-37=8-67 | | 1010=20x+70 | | 2x-4x+9+2=27 | | 8+3n-5=7n+12-3n | | -2v-34=6(v+5) | | 40-7=60+9 | | 13(5x+4)=-14(x-5) | | 1.60m+60=1.35m+61 | | 7g+8g-2= | | 10(8x+6)=-13(x-3) | | 2(x-7)+2=-12 | | [6k]=7 | | 10(-14x+8)=-13(x-2) | | 10(-14x+8)=-12(x-2) | | 8+4=15-10 | | 2(4w-7)=8 | | 9+7n-5n= | | 2(-18)-5=x |